(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, the effect of various new physiologically active substances on the cotton plant during certain stages of its development is studied, the effect on plant growth, development, cotton yield and changes in the leaf surface is studied. stated about. The effect of methods and periods of application of "Avangard start" and "Gulliver" biostimulants in cotton care on changes in cotton yield was studied on the basis of phenological observations in laboratory and field conditions.